2019
DOI: 10.1007/s00234-019-02238-5
|View full text |Cite
|
Sign up to set email alerts
|

White matter alterations in adult with autism spectrum disorder evaluated using diffusion kurtosis imaging

Abstract: Autism spectrum disorder (ASD) has been related to the impairments of white matter (WM) pathways.Recently, a two-compartment model of diffusion kurtosis imaging (DKI) was used to analyze the WM in ASD.However, the model is restricted by some limitations. Our study aimed to demonstrate the first use of a modelfree conventional DKI in the evaluation of WM in ASD and to test the relationship between WM alterations and personality scales. MethodsFifteen subjects with ASD (ASDs) and 15 neurotypical controls (NTs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…Previous studies that used varied approaches to diffusion-weighted imaging data have found evidence for WM microstructural abnormalities in adults with autism in the ATR [ 3 , 4 ], ALIC [ 23 ], CC [ 2 , 4 6 , 21 , 22 , 24 , 49 ], cingulum [ 2 , 3 , 21 , 24 ], forceps minor and major [ 21 ], IFOF [ 4 , 21 , 22 , 49 ], ILF [ 3 , 4 , 21 , 22 , 49 ], SLF [ 3 , 4 , 21 23 , 49 ], and UF [ 2 4 , 21 , 49 ], which is broadly neuroanatomically consistent with our findings. This shows the robustness of the diffusion MRI data analysis pipeline used in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies that used varied approaches to diffusion-weighted imaging data have found evidence for WM microstructural abnormalities in adults with autism in the ATR [ 3 , 4 ], ALIC [ 23 ], CC [ 2 , 4 6 , 21 , 22 , 24 , 49 ], cingulum [ 2 , 3 , 21 , 24 ], forceps minor and major [ 21 ], IFOF [ 4 , 21 , 22 , 49 ], ILF [ 3 , 4 , 21 , 22 , 49 ], SLF [ 3 , 4 , 21 23 , 49 ], and UF [ 2 4 , 21 , 49 ], which is broadly neuroanatomically consistent with our findings. This shows the robustness of the diffusion MRI data analysis pipeline used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Autism is a neurodevelopmental condition characterized by social communication and interaction deficits and the presence of restricted and repetitive patterns of behaviors, interests, or activities [ 1 ]. Evidences suggesting the association between behavioral anomalies in autism and white matter (WM) microstructural alterations that persist until adult life are increasing [ 2 6 ]. Although the pathophysiological causes of autism are not yet fully understood, recent postmortem studies support the view that neuronal loss [ 7 , 8 ] and neuroinflammation [ 9 , 10 ] contribute to autism etiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DKI describes the state of brain tissue using three kurtosis metrics: mean kurtosis (MK), axial kurtosis (AK), and radial kurtosis (RK). DKI has been used to evaluate neurodegeneration in WM with complex structures, including voxels containing crossing fibers [ 12 , 35 , 36 , 37 ]. Moreover, DKI parameters reflect the restriction of water diffusion in anisotropic as well as isotropic environments compared to DTI parameters, which assume non-restriction of water diffusion; therefore, the utility of DKI has also been demonstrated for the evaluation of microstructural changes in GM, which is composed primarily of neuronal cell bodies and exhibits isotropic water diffusion [ 20 , 28 , 38 , 39 ].…”
Section: Diffusion Mri Techniquesmentioning
confidence: 99%
“…One possible explanation for this finding is that the arcuate and temporoparietal tracts mature in later childhood, and the younger age of our participants may have not allowed us to observe this maturation yet. Furthermore, the corpus callosum (CC) plays an important role in the lateral asymmetry of brain function [26][27][28][29] as the main transverse fibers between bilateral cerebral hemispheres. Abnormal development of the CC may affect the integration and communication of information between the hemispheres, affecting cognitive function in ASD.…”
mentioning
confidence: 99%